Rapid cue-specific remodeling of the nascent axonal proteome - Cagnetta, Roberta; Frese, Christian K.; Shigeoka, Toshiaki; Krijgsveld, Jeroen; Holt, Christine E. (Neuron, 2018)
Axonal protein synthesis and degradation are rapidly regulated by extrinsic signals during neural wiring, but the full landscape of proteomic changes remains unknown due to limitations in axon sampling and sensitivity. By combining pulsed stable isotope labeling of amino acids in cell culture with single-pot solid-phase-enhanced sample preparation, we characterized the nascent proteome of isolated retinal axons on an unparalleled rapid timescale (5 min). Our analysis detects 350 basally translated axonal proteins on average, including several linked to neurological disease. Axons stimulated by different cues (Netrin-1, BDNF, Sema3A) show distinct signatures with more than 100 different nascent protein species up- or downregulated within the first 5 min followed by further dynamic remodeling. Switching repulsion to attraction triggers opposite regulation of a subset of common nascent proteins. Our findings thus reveal the rapid remodeling of the axonal proteomic landscape by extrinsic cues and uncover a logic underlying attraction versus repulsion.
Gesehen am 26.03.2020